Cicero in 17th, 18th, and 19th Century Painting: A Witness to the Survival of His Works and Those of Sallust, Plutarch, and Cassius Dio - Martín Puente, Cristina (Ciceroniana On Line, 2021)
Cicero has had a great influence on writers and intellectuals of all periods. Because of his enormous importance, he also has been portrayed in sculpture, painting, manuscripts and other artistic disciplines. His imprint is enormous among Enlightenment writers and thinkers, as an intellectual and political model, and it is present in philosophical, dramatic, and other works. In this paper, his appearance in pictures of large format is developed, between the 17th and 19th centuries, which give indications of the reception of the Tusculan Disputations, De legibus, In Verres, Catilinarians, and Pro Ligario, and, as well, of the Catilinarian Conspiracy of Sallust, of the Life of Cicero of Plutarch, and of the Roman History of Cassius Dio.